Соціально-правове становище наукової інтелігенції Житомирщини у 20–30-х рр. ХХ ст. - Novosadova, Natalia; Новосадова, Наталія (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті подано основні аспекти життя наукової інтелігенції Житомирщини протягом 20–30-х років ХХ ст. Наведено основні джерела формування місцевої інтелігенції. Здійснено кількісний зріз регіону за національни-ми особливостями. Висвітлено їх соціально-правове становище в зазначений період.. The article presents the characteristics of the socio-legal status of members of the scientific intelligentsia of the city and rural Zhytomyr during the 20’s - 30’s of ХХ century. The ways of formation of the local elite. A quantitative analysis based on ethnicity. Highlights the political mood of the «old» and «new» intellectuals to the Soviet authorities. Noted especially from rural location and scientific intellectuals in political and economic campaigns, awareness-raising and in the process of liquidation of the kulaks as a class. The features of the relationship of the local intelligentsia with power.
Socio-legal Status of Scientific Intelligentsia Zhytomyr in 20–30th Years of the ХХ Century
Keywords: інтелігенція; наукова інтелігенція; освіта Житомирщини; національні меншини; «інако-мислення»; intelligence; scientific intelligence; education of Zhytomyr; national minorities; «dissent»